New models of urbanity in the in-between condition, village of Chucher, Skopje - Maksim Naumovski; Pavel Veljanoski; Miroslav Pejovski (University American College Skopje, 2021)
The doctrines of urban plans of the last century imposed on the territory of the city of Skopje have always insisted on a hierarchical and structured character of the city and its parts. The unattainability to establish one consistent urban model in this period leads us to a new reading of the relationship of the city and its territory, one that is a programmatic unity/difference of particularities and their power. This distinctiveness in its full capacity is most explicitly recognized in the contact of the city and its natural and built periphery. In the specific urban, economic, cultural, social and post-pandemic conditions of our cities, the landscape in its full productive and phenomenological scales can be a structural element for observation and intervention in the territory. Although similar processes affect the periphery, the issues related to its sustainable development are considered in terms of specific territorial scope, the village of Chucher in the area of Crnogorija as an example of a recontextualized environment on the outskirts of Skopje. Building on subjective and empirical research and documentation of the territory, we operationalize the landscape through its dominant element, the topography. The superposition of all this information generated positions of architectural, programmatic, infrastructural, the natural density that sometimes builds on the old position of the existing features and sometimes proposes new ones. These new models of urbanity that predetermine different cultural and social relationships provide forms and spatial structures that create neighborhoods and social relation in direct contact with the openness of the landscape. In the context that is subject to daily changes and transformations that cause dramatic spatial consequences, the aim of this paper promotes an interdisciplinary approach through the symbiosis between actors and structures of biodiversity, agriculture, industry, housing and work as a prerequisite for resilient city models.
Keywords: 330; periphery; landscape; community; adaptive infrastructure; post-pandemic